Juegos y su impacto en el desarrollo emocional de los niños de Educación Inicial II - Carpio Lavayen, Erik Josbel (2025)
This research is titled "Games and their impact on the Emotional Development of children in Early Childhood Education II", because it is directly related to the research lines of the Technical University of Babahoyo. In Academic Domain: Education and Society, with the research line of the Technical University Babahoyo: Pedagogy and Educational Innovation, in turn the research subline of the University: Pedagogical approach and innovation in educational practices and the research subline of the career: Early Childhood Education based on competencies and projects. whose objective was to determine the impact of games on the emotional development of children in Early Childhood Education II where to fulfill the same a non-experimental methodological design of a transversal type was executed, with a descriptive-explanatory approach, using an inductive method and a mixed approach. These types of research include documentary and field research. This is allowing us to establish that the game plays an important role in the growth of children of Initial Education II of the Juan E. Verdesoto Educational Unit, because it represents a natural method to acquire knowledge and express emotions... Through it they can interact with their environment and with their peers, learning to manage circumstances that are sometimes complicated for them... In addition, it gives them the possibility of cultivating social and emotional skills while having fun in the activities, which encourages them to get involved in an active way.